2016
DOI: 10.1186/s12940-016-0113-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood lead and cadmium levels associated with chronic infections among non-smokers in a cross-sectional analysis of NHANES data

Abstract: BackgroundExperimental animal studies, in vitro experiments, and clinical assessments have shown that metal toxicity can impair immune responses. We analyzed data from a United States representative National Health and Nutrition Examination Survey (NHANES) to explore associations between chronic infections and elevated blood concentrations of lead and cadmium among non-smoking NHANES participants.MethodsNHANES data from 1999 to 2012 were examined and weighted to represent the United States population. Multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…Studies have found that exposure to heavy metals and other trace elements may compromise various aspects of the immune system. Among these elements, arsenic (As), cadmium (Cd) and lead (Pb) have received more attention and investigations [ 1 , 2 , 3 , 4 , 5 , 6 ]. Cell culture study shows that the chemotherapeutic agent arsenic trioxide could inhibit early T cell cytokine production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that exposure to heavy metals and other trace elements may compromise various aspects of the immune system. Among these elements, arsenic (As), cadmium (Cd) and lead (Pb) have received more attention and investigations [ 1 , 2 , 3 , 4 , 5 , 6 ]. Cell culture study shows that the chemotherapeutic agent arsenic trioxide could inhibit early T cell cytokine production.…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies have observed effects of trace elements on humans using immunologic indicators. The cross-sectional study using National Health and Nutrition Examination Survey (NHANES) data from 1999 to 2012 showed that elevated blood levels of Pb and Cd might increase the susceptibility to chronic infections [ 6 ]. Workers with higher Pb exposure may have depressed T helper lymphocytes, IgG, IgM and C3, C4 complement levels, chemotaxis, and random migration of neutrophils [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lead inhalation and ingestion is attributed to tobacco, construction, hazardous waste, and industrial sites making batteries, ammunition, and roofing materials, whereas cadmium may be ingested from vegetables contaminated with fertilizer (Krueger and Wade, 2016). Even chronic, low dose heavy metal exposure poses a substantial public health concern because chronic inflammatory skin diseases are exacerbated with pollution exposure (Araviiskaia et al, 2019;Wang and Fowler, 2008).…”
Section: Elevated Blood Heavy Metals In Pruritic Dermatosesmentioning
confidence: 99%
“…It is believed that smoking contributes in increasing the blood concentration of some heavy metals such as cadmium (Cd) [4,5], lead (Pb) [4] and chromium (Cr) [6]. Many heavy metals are known to have adverse impact on human's health, even at relatively low-level exposures [7], and are suspected of causing cancer and many other life-threatening diseases such as cardiovascular diseases [8].…”
Section: Introductionmentioning
confidence: 99%
“…For Cd, The major exposure sources in humans are food consumption and smoking [7], and since lungs absorb cadmium better than the gastrointestinal tract [9], it is expected that there is higher exposure to cadmium from smoking rather from food consumption. Through smoking, cadmium enters the lungs then builds up in tissues, particularly the liver and kidneys [10].…”
Section: Introductionmentioning
confidence: 99%